EVALUASI PROGRAM PROYEK PENANGGULANGAN KEMISKINAN PERKOTAAN (P2KP) DI KABUPATEN KLATEN - AGUS PURWANTO (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2015)
This study aims to determine (1) Implementation of the Urban Poverty Project (P2KP) and the level of social welfare Klaten district (2) Impact of Urban Poverty Project (P2KP) to the betterment of society, the increase in revenue, to the creation of employment opportunities in the district of Klaten. This research was conducted in Klaten district to take an object or area of ​​the District who receive assistance P2KP. In Klaten district area that receives no aid P2KP 7 subdistricts of 26 districts. Data analysis tool used is by using the t test. The results of the study concluded that the general implementation of the Urban Poverty Project (P2KP) in the district of Klaten went well. It was based on the descriptive statistical analysis showed that the program objectives P2KP in the right category. The target precision show proper category. The accuracy of the use of funds in the category of right show, refunds showed in the category of very precise. And training effort shows in the right category. Program P2KP significantly affect the income and employment of the population in seven Districts get help P2KP. It can be known from the results of t-test each of which gained value sig (significant) 0,000 smaller than α = 5%.